2018
DOI: 10.3892/ijo.2018.4579
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CD147 induces malignant melanoma cell apoptosis via the regulation of IGFBP2 expression

Abstract: Cluster of differentiation (CD)147, as a transmembrane glycoprotein, is highly expressed in a variety of tumors. Accumulating evidence has demonstrated that CD147 serves critical roles in tumor cell death and survival; however, the underlying mechanism requires further investigation. In the present study, it was revealed that CD147 knockdown significantly increased melanoma cell apoptosis. In addition, downregulation of CD147 reversed the malignant phenotype of melanoma, as demonstrated by the induction of tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Studies by Lu et al (53) and de la Iglesia et al (54) demonstrated that BSG overexpression was highly associated with poor prognosis of lung adenocarcinoma and breast cancer by stimulating the production of matrix metalloproteinases. Zhao et al (55) demonstrated that downregulation of BSG induced malignant melanoma cell apoptosis via the regulation of IGFBP2 expression. Lu et al (53) revealed that basolateral CD147 induced hepatocyte polarity loss by E-cadherin ubiquitination and degradation in the progression of hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Lu et al (53) and de la Iglesia et al (54) demonstrated that BSG overexpression was highly associated with poor prognosis of lung adenocarcinoma and breast cancer by stimulating the production of matrix metalloproteinases. Zhao et al (55) demonstrated that downregulation of BSG induced malignant melanoma cell apoptosis via the regulation of IGFBP2 expression. Lu et al (53) revealed that basolateral CD147 induced hepatocyte polarity loss by E-cadherin ubiquitination and degradation in the progression of hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in the expression of IGFBP-2 in lung cancer cells 39 , breast cancer cells 42 , and cervical cancer cells 43 increased the proliferation of cells. Conversely, decrease in the expression of IGFBP-2 in skin cancer cells 44 and colorectal cancer cells 45 decreased the proliferation of cells. In these cancer cells, IGFBP-2 acts as an oncogene, and the decrease in cell viability by AOFE treatment may be attributed to the possibility that the expression of IGFBP-2 may be regulated by AOFE treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, CD147 acts as a key role in mediating tumor cell invasiveness via regulating MMP expression, such as MMP-2 and MMP-9 in adjacent cancer cells or CAFs ( 25 , 26 ). One study indicated that CD147 could induce malignant melanoma cell apoptosis through IGFBP2 and PTEN/PI3K/AKT signaling pathway ( 27 ). In a HNSCC xenograft model, Binbin Yu et al.…”
Section: Discussionmentioning
confidence: 99%